Future biogeochemical forcing in Eastern Siberia: cooling or warming? - Arneth, A.; Olin, S.; Makkonen, R.; Paasonen, P.; Holst, T.; Kajos, M.; Kulmala, M.; Maximov, T.; Miller, P. A.; Schurgers, G. (European Geosciences Union, 2014)
Over-proportional warming in the northern high latitudes, and large carbon stocks in boreal and (sub)arctic ecosystems have raised concerns as to whether substantial positive climate feedbacks from biogeochemical process responses should be expected. Such feedbacks occur if increasing temperatures lead to e.g., a net release of CO2 or CH4. However, temperature-enhanced emissions of biogenic volatile organic compounds (BVOC) have been shown to contribute to a cooling feedback via growth of secondary organic aerosol (SOA), and related aerosol forcings. Combining measurements in Eastern Siberia with model-based estimates of vegetation and permafrost dynamics, BVOC emissions and aerosol growth, we show here that the additional climate forcing from changes in ecosystem CO2 balance and BVOC-SOA interactions nearly cancel on a regional scale. The interactions between emissions and vegetation dynamics that underlie individual forcing estimates are complex and highlight the importance of addressing ecosystem-climate feedbacks in consistent, process-based model frameworks that account for a multitude of system processes.